Inversores fotovoltaicos trifásicos não isolados conectados à rede com técnicas para redução da corrente de fuga - Giacomini, Julian Cezar (2018)
This doctoral dissertation presents contributions related to transformerless grid-connected three-phase photovoltaic systems, focusing on the leakage current reduction. Among the leakage current reduction techniques, the use of modified LCL (MLCL) filter brings important benefits, such as: maintenance of the voltage synthesis capability of the inverter and topology and modulation strategy do not require any modification. However, this filter presents some peculiarities, mainly in their design and resonance peaks damping. Therefore, a damping technique is required to reduce the leakage current without causing instability problems. Although the passive damping presents a simple implementaion and low cost, it causes leakage current rise and reduces the system efficiency. In this sense, an active damping technique using state feedback in αβ0 coordinates applied to a grid-connected three-phase multilevel inverter with MLCL filter is presented aiming to damp the filter resonances, keeping the leakage current attenuation and increasing the system efficiency. The αβ-axis control system damps the resonance peaks of the differential circuits, controls the grid currents and rejects some periodical grid disturbances, while the 0-axis control system damps the resonance peak located at low frequencies in the common mode circuit. In this way, the highfrequency leakage current attenuation is preserved, while the low-frequency attenuation is improved. A reduced-order states observer for the filter capacitors voltages is designed to reduce the number of voltage sensors. Since the MLCL filter also attenuates the grid current harmonics, a design methodology that integrates the requirements of leakage current and grid harmonic distortion is proposed. At the end, an analysis of discontinuous Pulse Width Modulation (PWM) techniques applied to the grid-connected three-phase inverter is performed to reduce the switching losses and, consequently, improve its efficiency. In this case, a modified discontinuous PWM modulation is proposed to reduce the impact on the leakage current of the photovoltaic system. Additionally, a hybrid damping for the MLCL filter is proposed to preserve the characteristics of the modified modulation, where the αβ-axis is actively damped and the 0-axis is passively damped. It is shown that is possible to improve the system efficiency through the proposed modulation keeping a low leakage current. Simulation and experimental results reinforce the theoretical conclusions related to the active damping technique, MLCL filter design and the application of the discontinuous PWM modulation.